2020
DOI: 10.1055/a-1268-8458
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study of Whole-body Vibration on Lipid Metabolism of Skeletal Muscle in Aging Mice

Abstract: Ageing increases the occurrence and development of many diseases. Exercise is believed to be an effective way to improve ageing and skeletal muscle atrophy. However, many elderly people are unable to engage in active exercise. Whole-body vibration is a passive way of moving that is especially suitable for the elderly and people who find it inconvenient to exercise. Metabolomics is the systematic study of metabolic changes in small molecules. In this study, metabolomics studies were performed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Interestingly, triglyceride levels were lower after completing a WBV (AMAXS AEX 2022, Chase Co., Ltd., Bangkok, Thailand) session. This finding is in agreement with previous studies showing a reduction in triglyceride levels after WBV training in obese and old mice [ 23 , 24 , 25 ]. A vibration stimulus generates force to the muscle via oscillatory motion, leading to muscle activation [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, triglyceride levels were lower after completing a WBV (AMAXS AEX 2022, Chase Co., Ltd., Bangkok, Thailand) session. This finding is in agreement with previous studies showing a reduction in triglyceride levels after WBV training in obese and old mice [ 23 , 24 , 25 ]. A vibration stimulus generates force to the muscle via oscillatory motion, leading to muscle activation [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…While this literature points out several health advantages, little is known about the effects of WBV on metabolic-related outcomes. Most previous studies conducted in animal models have evident beneficial effects of WBV on lipid mobilization, such as lowering cholesterol and triglycerides [ 23 , 24 , 25 ]. In addition, a previous study focusing on the acute effects of warm-up with vibration before (AER) on fat oxidation found that an additional WBV during warm-up had greater fat oxidation than warm-up without vibration in obese men [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To acquire knowledge of muscle wasting, Senoo et al adopted a metabolomic method to explore the glycerophospholipid profile of skeletal muscle in a muscular dystrophy model using a denervation murine, and they found an apparent alteration of glycerophospholipids [ 41 ]. Jiang et al reported that whole-body vibration, which is a special exercise for elderly people, had an impact on glycerophospholipid metabolism to reduce lipid deposition in aging muscles [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the biological processes responsible for physiological adaptations to WBV is a key step in the development of appropriate vibratory training protocols tailored to personal needs. Indeed, WBV could be used as a form of passive training for patients unable to exercise, to prevent and/or counteract the cognitive and motor decline associated with sedentariness and the progression of chronic degenerative diseases [ 38 ]. To the best of our knowledge, this is the first experimental study to determine whether exposure to WBV for 3 months can modulate the FNDC5 expression, together with that of tissue-specific markers such as BDNF, myostatin, and COL-1 in the brain, muscle, and bone tissue, respectively.…”
Section: Discussionmentioning
confidence: 99%